DNA elution from buccal cells stored on Whatman FTA Classic Cards using a modified methanol fixation method. (April 2009) - Johanson, Helene C.; Hyland, Valentine; Wicking, Carol; Sturm, Richard A.
We describe here a method for DNA elution from buccal cells and whole blood both collected onto Whatman FTA technology, using methanol fixation followed by an elution PCR program. Extracted DNA is comparable in quality to published Whatman FTA protocols, as judged by PCR-based genotyping. Elution of DNA from the dried sample is a known rate-limiting step in the published Whatman FTA protocol; this method enables the use of each 3-mm punch of sample for several PCR reactions instead of the standard, one PCR reaction per sample punch. This optimized protocol therefore extends the usefulness and cost effectiveness of each buccal swab sample collected, when used for nucleic acid PCR and genotyping.